2008
DOI: 10.1038/oby.2008.420
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Predictors of Inflammation, Adhesion, and Coagulability in Healthy Younger‐aged Adults

Abstract: Elevated levels of inflammatory biomarkers are associated with the pathophysiology of cardiovascular diseases and are predictors of cardiovascular events. The objective of this study was to determine the unique contributions of metabolic factors as predictors of inflammation (C‐reactive protein (CRP) and interleukin‐6 (IL‐6)), adhesion (soluble intercellular adhesion molecule‐1 (sICAM‐1)), and coagulation (D‐dimer) in healthy younger‐aged adults. Participants were 83 women and 92 men (mean age 30.04 years, s.d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…The lack of effect from drinking carrot juice on the plasma inflammatory markers as well as insulin and leptin may have been because insulin, leptin, interleukin-1α, and C-reactive protein were all within normal ranges. Our report is inconsistent with an earlier finding suggesting that elevated C-reactive protein was independently associated with higher BMI and higher triglycerides [ 45 ]. However, our results are consistent with those who reported that the mean values of cholesterol, triglycerides, and LDL cholesterol were not affected by increased C-reactive protein and insulin in obese women when compared to normal weight controls suggesting that the increase in inflammatory markers have no effect on lipid panel status [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of effect from drinking carrot juice on the plasma inflammatory markers as well as insulin and leptin may have been because insulin, leptin, interleukin-1α, and C-reactive protein were all within normal ranges. Our report is inconsistent with an earlier finding suggesting that elevated C-reactive protein was independently associated with higher BMI and higher triglycerides [ 45 ]. However, our results are consistent with those who reported that the mean values of cholesterol, triglycerides, and LDL cholesterol were not affected by increased C-reactive protein and insulin in obese women when compared to normal weight controls suggesting that the increase in inflammatory markers have no effect on lipid panel status [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Circulating levels of plasma CRP, IL-6, and sICAM-1 were determined by multiplex enzyme-linked immunosorbent assay with two sets of internal controls (Meso Scale Discovery Pro-Inflammatory I Panel, with Sector Imager 2400, Gaithersburg, Maryland). Inter- and intra-assay coefficients of variation were < 10% (50). …”
Section: Methodsmentioning
confidence: 97%
“…Circulating levels of CRP, IL-6 and TNF-α were determined in non-freeze thawed samples by commercial enzyme-linked immunosorbent assay (MSD, Gaithersburg, Maryland). The intra-assay and inter-assay coefficients of variation are less than 5% and 8%, respectively [58]. Urinary cortisol levels were determined by a commercial radioimmunoassay (Diagnostic Products Corporation, Los Angeles, CA), with intra- and inter-assay CVs of <4% and <7%, respectively.…”
Section: Methodsmentioning
confidence: 99%